Pengaruh Motivasi, Akreditasi Prodi, Fasilitas Pendidikan, Konsentrasi Jurusan, Biaya Pendidikan dan Reputasi Pendidik Terhadap Minat Mahasiswa untuk Melanjutkan Magister Akuntansi (Studi Empiris pada Mahasiswa Akuntansi di UMS) - Verawati, Dita; , Zulfa Irawati., SE., MSi (2016)
Higher education of Accountancy which does not yield professionalism as accountant will was not saleable in labor market. For the reason required by grad with the higher level education that was Magister Accountancy. Some factor influencing student enthusiasm to continue the Magister Accountancy among others was motivation, accreditation of study program, education facility, major's concentration, expense of education, and educator reputation. This research was aim to identify the influence of motivation, accreditation of study program, education facility, major's concentration, expense of education, and educator reputation toward student enthusiasm to continue the Magister Accountancy. Research takes the object of accountancy student in students of semester 7 Muhammadiyah Surakarta University, so that obtained 50 students sampel who was taken by purposive sampling. The data source in the form of primary data obtained from questioner. The data analyze was used cover data quality test, classic assumption test, multiple linear regressions analyze and hypothesis test covering F test, coefficient determinasi R2 test, and t test. The results of analysis can be conclusion that the factors influencing student enthusiasm to continue the Magister Accountancy including motivation, accreditation of study program, education facility, major's concentration, expense of education, and educator reputation. So that can be interpreted that sixth of the independent variable have an effect on significant toward student enthusiasm to continue the Magister Accountancy, this matter was shown by p value was each variable < 0,05. So that hypothesis from H1 until H6 was truth acceptable.